Listen up Philip - DeWitt, Keegan 1982- (Eureka Entertainment, 2015)
"Combining intellectual ambition with a singular comic sensibility, the third feature film by writer-director Alex Ross Perry marked a defining moment for the American independent cinema of the 2010s. As with his previous features "Impolex" and "The Color Wheel", the blackly hilarious "Listen Up Philip" is distinguished as much by its literary pedigree as by its fine attunement to atmosphere, sense of place, and, enabled by the camerawork of Sean Price Williams, the texture of the image. [...]." [amazon.de]
Bildformat 1.85:1 1080p AVC encode
Keywords: Blu-Ray-Disc